The culture and nature assets. The current crossovers and the agenda for the future - Marciniak, Arkadiusz (Ex Novo: Journal of Archaeology, 2019)
The paper intends to provide an overview of major crossovers between cultural and natural heritage appearing and executing in political, administrative, economic, societal and academic domains. It discusses complicated processes that have led to overcoming a separation between these two largely distinct domains, which is strikingly embedded in western philosophy. The relevance of such crossovers is examined in the context of challenges imposed by the climate change and major shifts in the understanding of heritage and its role in the society. It concludes by providing some thoughts on the character of the future crossovers between cultural and natural heritage more effectively engaging with the contemporarily emergent issues of social significance.